Analisis Kompetensi Calon Sekretaris pada Perusahaan di Indonesia - Fenny Damayanti; sofiatiningsih sofiatiningsih (Jurnal Sekretaris dan Administrasi Bisnis, 2020)
This study entitled the analysis of the competency of candidates for secretaries in companies in Indonesia. The results showed that the competencies needed for a candidate for secretary is to have an attitude that has a value above the average. Because the secretary's job is 80% to communicate, serve stakeholders according to their level. Therefore all lecturers need to provide motivation, direction in each learning process regarding the importance of attitude. Institutions are expected to facilitate by creating a conducive environment so that students have the habit to behave and behave well in their daily activities. Lecturers in this case are expected to be an example for female students.